1994
DOI: 10.1139/f94-190
|View full text |Cite
|
Sign up to set email alerts
|

Shift in the Intestinal Microflora of Atlantic Halibut (Hippoglossus hippoglossus) Larvae during First Feeding

Abstract: Bergh, IZI., K.E. Naas, and T. Harboe. 1994. Shift in the intestinal microflora of Atlantic halibut (Hippoglossus hippoglossus) larvae during first feeding. Can. J. Fish. Aquat. Sci. 51 : 1899-1 903.Isolates of aerobic intestinal bacterial flora from unfed Atlantic halibut (Hippoglossus hippoglossus) larvae revealed a population dominated by nonfermentative rods of the Cytophag~Flexibacter/Flavobacteriurn group. Following the onset of feeding, the flora gradually changed towards a fermentative flora dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 18 publications
1
31
0
2
Order By: Relevance
“…It was suggested by Naas et al (1992) that the nutritional effects of the algae are of minor importance in comparison with their effect on physical parameters, in particular light regime. This hypothesis is partially supported by the finding of Bergh et al (1994) that the shift from a nonfermentative towards a fermentative intestinal bacterial microflora occurred faster in larvae in water to which algae had been added than in larvae kept in water without algal addition.Intensive first feeding of halibut is based on Artemia spp. as live-feed organisms.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…It was suggested by Naas et al (1992) that the nutritional effects of the algae are of minor importance in comparison with their effect on physical parameters, in particular light regime. This hypothesis is partially supported by the finding of Bergh et al (1994) that the shift from a nonfermentative towards a fermentative intestinal bacterial microflora occurred faster in larvae in water to which algae had been added than in larvae kept in water without algal addition.Intensive first feeding of halibut is based on Artemia spp. as live-feed organisms.…”
mentioning
confidence: 80%
“…are less frequent (Hansen & Olafsen 1989, Bergh 1995. The composition of the intestinal bacterial flora associated with yolk-sac larvae resembles the egg epiflora, whereas a shift in the intestinal microflora from a generally nonfermentative towards a fermentative flora dominated by the Vibrio/Aeromonas group coincides with the onset of exogenous feeding (Bergh et al 1994, Bergh 1995.…”
Section: Bacterial Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Live prey (rotifer and Artemia) are important carriers of contamination of the larval digestive tract (Muroga et al, 1987;Nicolas et al, 1989;Cahill, 1999;Bergh et al, 1994;Blanch et al, 1997;Ringø and Birkbeck, 1999), which greatly determines the microbiota of the larvae and in many cases is responsible for significant mortality rates (Campbell and Buswell, 1983;Muroga et al, 1987;Grisez et al, 1997. In some studies, alternative methods (eggs disinfection, use of microbially-matured water or baths of prey in tap water) to antibiotics have been considered (Vadstein et al, 1993;Planas and Cunha, 1999;Skjermo and Vadstein, 1999) in order to reduce the microflora which accompanies the prey, but also the delivery of probiotic bacteria (Gatesoupe, 1991;;Gatesoupe, 1997;Harzevili et al, 1998;Gómez-Gil et al, 1998;Makridis et al, 2000;Gatesoupe, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…intestinal flora to an Aeromonas spp./Vibrio spp. dominant flora occurred when first feeding commenced (Bergh et al, 1994). It indicated that the gut microbiota of aquatic animals may change rapidly with the intrusion of microflora from water, live food and artificial diet.…”
Section: Probiotics Effects In Aquaculture: Benefits To the Healthmentioning
confidence: 99%